2021
DOI: 10.21203/rs.3.rs-348506/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Causes of Meatal Stenosis in Circumcised Boys

Abstract: The aim of this study was to investigate the prevalence and causes of meatal stenosis after circumcision in children. Between October 2018 and April 2019, we carried out a prospective cross-sectional study on 1031 circumcised boys, aged 5 to 8 years (mean age 6.1 years ± 0.3 years), enrolled in the first level of primary school in Oran (Algeria). All enrolled children underwent a genitourinary examination. Moreover, an anonymous questionnaire was filled-in by one of the parents. The screening revealed the pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The authors tend to favor circumcision because of its numerous advantages. A recent study carried out in Algeria found out that meatal stenosis is more common when circumcision is carried out in the first week, there is use of healing agents and when there is prior adhesion of the foreskin to the glans [32]. In our hospital we used petroleum jelly after circumcision and also after surgery for meatal stenosis.…”
Section: Discussionmentioning
confidence: 97%
“…The authors tend to favor circumcision because of its numerous advantages. A recent study carried out in Algeria found out that meatal stenosis is more common when circumcision is carried out in the first week, there is use of healing agents and when there is prior adhesion of the foreskin to the glans [32]. In our hospital we used petroleum jelly after circumcision and also after surgery for meatal stenosis.…”
Section: Discussionmentioning
confidence: 97%